UMKM Akuntansi Terdata: Pendataan dan Pelatihan untuk Fondasi Keuangan Kuat dan Pertumbuhan Bisnis - trisnaning (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2025)
Recorded MSME Accounting: Data Collection and Training for a Strong Financial Foundation and Business Growth. This report investigates UMKM (Usaha Mikro, Kecil, dan Menengah) play a crucial role in the economy, yet many still face challenges in financial management due to the lack of a structured accounting system. The Recorded UMKM Accounting Program aims to strengthen the financial foundation of UMKM through comprehensive financial data collection and accounting training. This program includes business financial data recording, basic financial bookkeeping training, the use of fundamental accounting software, and financial statement preparation. The results indicate that UMKM participating in this program experience significant improvements in financial transparency, cash flow management capabilities, and access to financing. Additionally, the training encourages business growth through better financial planning and increased operational efficiency. Thus, the Recorded UMKM Accounting Program not only reinforces the financial foundation of UMKM but also creates opportunities for business expansion and long-term sustainability.